2019
DOI: 10.2176/nmc.st.2018-0190
|View full text |Cite
|
Sign up to set email alerts
|

Parent Artery Occlusion for Unruptured Cerebral Aneurysms: Results of the Japanese Registry of Neuroendovascular Therapy 3

Abstract: Although the current standard treatment for unruptured aneurysms comprises surgical clipping or endovascular coiling, these techniques are not suitable for some cases, such as large, giant, and fusiform aneurysms. Endovascular parent artery occlusion (PAO), which includes internal trapping and proximal occlusion, is a well-established alternative treatment for such cases. Here, we retrospectively reviewed PAO cases from the Japanese Registry of Neuroendovascular Therapy 3, a nation-wide survey of all neuroendo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…Similar to our study, Nishi et al reported that high complete occlusion rate (90.5%, n = 248) with low morbidity (5.8%) and mortality (0.7%) rate was achieved in their study [20]. PAO can be a definitive and useful modality because (1) it is a simple technique and (2) it shows a high complete occlusion rate and low recurrence rate compared with other modalities [20,30]. However, patients treated with PAO were often exposed to inherent ischemic complications because of its destructive nature [20].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Similar to our study, Nishi et al reported that high complete occlusion rate (90.5%, n = 248) with low morbidity (5.8%) and mortality (0.7%) rate was achieved in their study [20]. PAO can be a definitive and useful modality because (1) it is a simple technique and (2) it shows a high complete occlusion rate and low recurrence rate compared with other modalities [20,30]. However, patients treated with PAO were often exposed to inherent ischemic complications because of its destructive nature [20].…”
Section: Discussionsupporting
confidence: 91%
“…PAO showed the highest complete occlusion rate (90.0%) and the lowest complication rate (12.5%) in this study. Similar to our study, Nishi et al reported that high complete occlusion rate (90.5%, n = 248) with low morbidity (5.8%) and mortality (0.7%) rate was achieved in their study [20]. PAO can be a definitive and useful modality because (1) it is a simple technique and (2) it shows a high complete occlusion rate and low recurrence rate compared with other modalities [20,30].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations